Effect of gamma radiation on the physico mechanical properties of recycled HDPE/modified sugarcane bagasse composite. Issue 2 (1st February 2019) - EL-Zayat, Mai M.; Abdel-Hakim, A.; Mohamed, Maysa A.
Abstract: In this work, the sugarcane bagasse (SCB) fibers were used as reinforcing filler for recycled high density polyethylene (rHDPE) to form eco-friendly composite. The SCB surface was chemically modified to improve the compatibility with rHDPE matrix. The SCB fibers were alkali modified using 10% sodium hydroxide (SCBm) and acetylated using acetic anhydride (SCBac). The chemically modified SCB fibers were characterized using Fourier transform infrared (FTIR) and scanning electronic microscopy (SEM). The composites were prepared by mixing of rHDPE with 15 phr (parts per hundred parts rHDPE) of different SCB samples. Neat rHDPE and its composites with SCB were irradiated by gamma radiation dose of 50–250 kGy. The Effect of gamma radiation on the water up-take, mechanical properties and the thermal stability of (rHDPE) and its composites was studied. The effect of gamma radiation on the compatibility between rHDPE and SCB was also investigated. The results showed that the combination between the chemical modification of fibers and the irradiation of polymer composites were more effective in compatibility improvement than chemical modification alone. The irradiated (at 100 kGy) composite containing of SCBac gave the best mechanical properties, lowest water up-take and the highest thermal stability.